2003
DOI: 10.1016/s0375-9601(03)01047-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantum deleting and signalling

Abstract: It is known that if we can clone an arbitrary state we can send signal faster than light. Here, we show that deletion of unknown quantum state against a copy can lead to superluminal signalling. But erasure of unknown quantum state does not imply faster than light signalling.Keywords: Linearity, cloning, deleting, signalling Two deep rooted concepts in quantum theory are linear superposition principle and linear evolution equations [1]. Linear superposition principle is the one which makes any two state quantu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
26
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…There have also been attempts to derive them by applying some other fundamental principles of nature, like no-faster-thanlight communication between spatially separated parties [8,9,10,11] and preservation of entanglement for closed systems under local operations [12]. Another important no-go theorem is the non-existence of a universal flipping operator (NOT gate) [13] which would take an arbitrary qubit state to its orthogonal complement.…”
Section: Introductionmentioning
confidence: 99%
“…There have also been attempts to derive them by applying some other fundamental principles of nature, like no-faster-thanlight communication between spatially separated parties [8,9,10,11] and preservation of entanglement for closed systems under local operations [12]. Another important no-go theorem is the non-existence of a universal flipping operator (NOT gate) [13] which would take an arbitrary qubit state to its orthogonal complement.…”
Section: Introductionmentioning
confidence: 99%
“…03.65.Wj Quantum bits (qubits) are fundamentally different from classical bits in that unknown qubits cannot be copied with unit efficiency [1,2,3] (no-cloning theorem). Another related property of qubits is that nonorthogonal qubits cannot be distinguished with certainty [4].Interestingly, however, it has been found that the nosignaling condition is entangled with other impossibility proofs [5,6,7,8]. In particular, it has been shown that no-signaling condition gives the same tight bound on probability of conclusive measurement as obtained by quantum mechanical formula [7].…”
mentioning
confidence: 99%
“…This is called no-deleting. Again the above statement of no-deleting can be proven as a theorem, by assuming a unitary evolution and was called the no-deleting theorem [21,22]. Note that from a formal point of view, it is not clear whether there is any common physical origin of the above theorems or a relationship between them.…”
mentioning
confidence: 99%
“…One may also see deletion in the following way (which is again not possible under unitary dynamics [22]):…”
mentioning
confidence: 99%